2015
DOI: 10.1155/2015/678765
|View full text |Cite
|
Sign up to set email alerts
|

Dictionary-Based, Clustered Sparse Representation for Hyperspectral Image Classification

Abstract: This paper presents a new, dictionary-based method for hyperspectral image classification, which incorporates both spectral and contextual characteristics of a sample clustered to obtain a dictionary of each pixel. The resulting pixels display a common sparsity pattern in identical clustered groups. We calculated the image’s sparse coefficients using the dictionary approach, which generated the sparse representation features of the remote sensing images. The sparse coefficients are then used to classify the hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Based on the similar idea, Kang et al [32] used stochastic rovers for probability majorization, which is demonstrated to be very useful when training samples are relatively restricted. In recent years, sparse representation also becomes a hot research topic in HIC field as a novel signal expression algorithm [33]- [37].…”
Section: Introductionmentioning
confidence: 99%
“…Based on the similar idea, Kang et al [32] used stochastic rovers for probability majorization, which is demonstrated to be very useful when training samples are relatively restricted. In recent years, sparse representation also becomes a hot research topic in HIC field as a novel signal expression algorithm [33]- [37].…”
Section: Introductionmentioning
confidence: 99%